2011
DOI: 10.4238/vol10-2gmr1100
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships of the Japanese persimmon Diospyros kaki (Ebenaceae) and related species revealed by SSR analysis

Abstract: ABSTRACT. Simple sequence repeat (SSR) molecular markers based on 18 primers were employed to study the genetic relationship of Japanese persimmon (Diospyros kaki) specimens. Two hundred and sixty-two bands were detected in 30 Japanese persimmon samples, including 14 Japanese and 10 Chinese genotypes of Japanese persimmon (Diospyros kaki) and six related species, D. lotus, D. glaucifolia, D. oleifera, D. rhombifolia, D. virginiana, and Jinzaoshi (unclassified -previously indicated to be D. kaki). All SSR pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Among the different molecular markers, SSRs, which are also called microsatellites, are the best-suited markers for genotyping the Diospyros genus (Luo et al, 2013). Guo and Luo (2006a, 2008, 2011 reported several SSR markers by ISSRsuppression PCR. Soriano et al (2006) developed 22 SSRs using a CT/AG-repeat-enriched library.…”
Section: Discussionmentioning
confidence: 99%
“…Among the different molecular markers, SSRs, which are also called microsatellites, are the best-suited markers for genotyping the Diospyros genus (Luo et al, 2013). Guo and Luo (2006a, 2008, 2011 reported several SSR markers by ISSRsuppression PCR. Soriano et al (2006) developed 22 SSRs using a CT/AG-repeat-enriched library.…”
Section: Discussionmentioning
confidence: 99%
“…were subjected to various doses of gamma rays, 15 and 20 gray from a 60 Co source. In this study, Naval et al [55] found that the most favorable gamma irradiation dose combining survival and mutation induction was 20 gray.…”
Section: Persimmon Breeding and Genetic Improvementmentioning
confidence: 99%
“…Breeding and Health Benefits of Fruit and Nut Crops that the placement of several Japanese cultivars within the European cultivar group suggests that European cultivars were developed from Japanese germplasm relatively recent and differences among cultivars are much greater than differences among cultivar groups regarding AFLP markers. In addition, Guo and Luo [60] indicated that SSR markers are a valuable tool for the estimation of genetic diversity and divergence in Diospyros.…”
Section: Biotechnology and Genomicsmentioning
confidence: 99%
“…The genus Diospyros has more than 500 species and is the largest genus of the Ebenaceae family. Diospyros has remarkable economic value, particularly Diospyros kaki L. (Ebenaceae), which is conventionally used as food in multiple countries (Guo and Luo, 2011).…”
Section: Introductionmentioning
confidence: 99%